Environmentally friendly water-based microfiber leather and its preparation method and application

By using the combination of antibacterial solutions and flame retardant solutions and WPU slurry in microfiber leather, the problem of insufficient antibacterial performance of existing microfiber leather is solved, and environmentally friendly water-based microfiber leather with high tensile strength, flame retardant performance and long-lasting antibacterial properties is achieved.

CN119777170APending Publication Date: 2025-04-08JIAN CITY SANLING MICROFIBER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411980881.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The antibacterial properties of existing microfiber leather are insufficient, making it difficult to meet the high requirements of versatile products for flame retardant, conductive, and radiation-proof properties.

Method used

By using the preparation method of environmentally friendly water-based microfiber leather, the ultra-fiber short fiber is soaked and absorbed in antibacterial solution and flame retardant solution to form a composite and combined with WPU slurry to form a leather with high tensile strength, flame retardant properties and long-lasting antibacterial properties.

Benefits of technology

It significantly improves the antibacterial and flame retardant properties of microfiber leather, while improving its tensile strength and wear comfort, meeting the high requirements of versatile products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119777170A_ABST
    Figure CN119777170A_ABST
Patent Text Reader

Abstract

The present invention discloses an environmentally friendly water-based microfiber leather and a preparation method and application thereof, and the present invention relates to the technical field of microfiber leather. The environmentally friendly water-based microfiber leather comprises the following components: microfiber staple fibers, flame retardant solution, antibacterial solution, and WPU slurry. The present invention prepares the antibacterial solution so that the amino and hydroxyl groups in its structure can interact with the microfiber staple fibers and WPU slurry to form hydrogen bonds and the like, thereby enhancing the internal structure and improving the tensile strength of the microfiber leather. At the same time, the antibacterial solution adheres to and penetrates the fiber surface, thereby enhancing the inter-fiber bonding force and improving the tear resistance. The antibacterial solution can interact with the negative charge of the microbial cell membrane, destroy the cell membrane and cause the death of the microorganism. Its degradation products can also interfere with the metabolism of the microorganism, slowly release the antibacterial components, and provide lasting antibacterial properties. The antibacterial agent can form microchannels between the fibers, which is conducive to the passage of water vapor, increases the hydrophilicity of the leather, and makes the water vapor easier to be absorbed and transmitted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ultra-fine leather, in particular to an environmentally friendly water-based ultra-fine leather and a preparation method and application thereof. Background Art

[0002] Due to its excellent natural properties, natural leather is widely used in daily necessities, industrial products, clothing and other industries. However, with the development of the economy, natural leather can no longer meet people's demand for leather, and artificial leather and synthetic leather came into being at this time. The full name of microfiber leather is "superfine fiber reinforced PU leather". It has the most similar properties to natural leather. It is a high-end leather among synthetic leathers and represents the development direction of artificial leather.

[0003] With the improvement of living standards, people have more and more requirements for fabrics. For example, fabrics for high-speed train seats have high requirements for flame retardancy, dripping resistance, and smoke density; fabrics for conductive gloves have high requirements for wear resistance and conductivity; and fabrics used in health care products have special requirements for radiation protection, antistatic, and good magnetism. In order to meet the versatility of these products, the existing process usually adds material particles with corresponding functional properties to wet polyurethane, and then impregnates them into the base cloth to obtain microfiber leather with various functions. However, the antibacterial properties of the microfiber leather prepared by the existing technical solution need to be improved; to this end, the present invention provides an environmentally friendly water-based microfiber leather and its preparation method and application to solve the above problems. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides an environmentally friendly water-based microfiber leather and a preparation method and application thereof, which solves the problems mentioned in the above background technology.

[0005] To achieve the above objectives, the present invention is implemented by the following technical scheme: an environmentally friendly water-based microfiber leather, the environmentally friendly water-based microfiber leather comprises the following components: microfiber staple fibers, flame retardant solution, antibacterial solution, WPU slurry;

[0006] Wherein, the preparation method of WPU slurry is:

[0007] Ⅰ. Mix 25-30g of polycarbonate diol and 10-18g of polytetrahydrofuran under vacuum dehydration at 85-95°C for 1.5-2h;

[0008] Ⅱ. Add 16.5-25 g of isophorone diisocyanate and raise the temperature to 70-80°C under a nitrogen atmosphere;

[0009] III. Under stirring conditions, add 1.2-2.5 g of dibutyltin dilaurate dropwise and keep the reaction warm for 3.5-4.5 hours;

[0010] IV. Cool down to 60-65°C, add 12-15g of acetone, then add 1.5-2.5g of 2,2-dihydroxymethylpropionic acid, 0.8-1.25g of 1,4-butanediol, and 1.2-2.8g of trimethylolpropane, and react for 10-15h respectively;

[0011] Ⅴ. Cool down to 35-45°C, add 0.85-1.3 g of triethylamine, and react for 20-35 min;

[0012] VI. Add 80-110 g of deionized water and 1-1.5 g of ethylenediamine, stir and react for 20-30 min, then rotary evaporate, place in a vacuum drying oven for vacuum degassing for 45-60 min, and obtain WPU slurry;

[0013] Among them, in the III, the stirring speed is 180-220r / min; in the VI, the stirring speed is 1000-1200r / min.

[0014] Preferably, the preparation method of the flame retardant solution is:

[0015] S1. Pour 4-((3-hydroxypropyl)imino)methylphenol and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide into anhydrous ethanol, raise the temperature to 75-95° C., and stir at a speed of 250-400 r / min to react for 4.5-6 h;

[0016] S2. After the reaction is completed, cool to room temperature, filter, wash with anhydrous ethanol 3-4 times, and then dry in a vacuum oven at 55-65°C to constant weight to obtain a flame retardant solution.

[0017] Preferably, during the preparation of the flame retardant solution, the added amounts of the components are: 9.5-12.5 g of 4-((3-hydroxypropyl)imino)methylphenol, 10.5-14 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 150-200 mL of anhydrous ethanol.

[0018] Preferably, in S1, the preparation process of 4-((3-hydroxypropyl)imino)methylphenol is:

[0019] S11, pouring p-hydroxybenzaldehyde and 3-aminopropanol into anhydrous ethanol and mixing evenly;

[0020] S12, heat the oil bath to 50-70°C, stir and react at a speed of 230-350 r / min for 1.5-2 h;

[0021] S13, cooling to room temperature, filtering, washing the reaction product with deionized water for 3-5 times, and finally drying it in a vacuum oven at 45-60° C. for 8-12 hours to obtain 4-((3-hydroxypropyl)imino)methylphenol.

[0022] Preferably, in the preparation process of the 4-((3-hydroxypropyl)imino)methylphenol, the added amounts of the components are: 12.2-16 g of p-hydroxybenzaldehyde, 7.5-9.5 g of 3-aminopropanol, and 125-160 mL of anhydrous ethanol.

[0023] Preferably, the preparation method of the antibacterial solution is:

[0024] (1) Soak chitosan in 40% sodium hydroxide solution for 20-24 hours and filter;

[0025] (2) Pour chloroacetic acid into 150-180 mL of isopropanol and stir to dissolve to obtain a mixed solution;

[0026] (3) After complete dissolution, the product filtered in (1) is poured into the mixed solution in (2) and reacted at room temperature for 24-36 hours;

[0027] (4) After the reaction is completed, hydrochloric acid is added dropwise to adjust the pH value of the solution to 7.0, and then anhydrous ethanol is added to precipitate a precipitate, and then the precipitate is washed with deionized water for 3-5 times, and finally placed in a drying oven at 45-55°C for drying;

[0028] (5) Pour the dried precipitate into a sodium hydroxide solution, heat it to 50-65°C in a water bath, stir and react for 18-24 hours, then add hydrochloric acid dropwise to neutralize to a pH of 7.8-8;

[0029] (6) Grinding, and then treating with a nano ultra-high pressure homogenizer for 20-30 minutes to obtain an antibacterial solution.

[0030] A method for preparing environmentally friendly water-based microfiber leather comprises the following preparation steps:

[0031] Step 1: Put the microfiber staple fibers into a sodium hydroxide solution for activation, and then add dilute hydrochloric acid to neutralize;

[0032] Step 2: immerse the treated microfiber staple fibers in an antibacterial solution, allow the microfiber staple fibers to fully absorb the antibacterial solution, and then squeeze out the antibacterial solution in the microfiber staple fibers;

[0033] Step 3, immersing the ultra-short fibers in a flame retardant solution again, allowing the ultra-short fibers to fully absorb the flame retardant solution, and then squeezing out the flame retardant solution in the ultra-short fibers to obtain an ultra-short fiber composite;

[0034] Step 4, washing the microfiber staple fiber composite until the pH value of the washing liquid is no more than 8, and then drying;

[0035] Step 5, weighing, combing, mixing, laying, pre-needling, positive and negative needling are performed in sequence to form a non-woven fabric with a three-dimensional structural network;

[0036] Step six: treat the non-woven fabric with plasma in a nitrogen atmosphere at a gas flow rate of 50 sccm, immerse it in the WPU slurry for 45-65 minutes, and then perform double dipping and double rolling on the non-woven fabric. Immerse the rolled base fabric in the prepared sodium sulfate solution for 3 minutes, and then pre-dry it with infrared. After 10-15 minutes, transfer it to a 100-110°C hot air oven for drying to obtain environmentally friendly water-based microfiber leather.

[0037] Preferably, in step six, the first pressure is 30 kg / cm 2 , the second pressure is 10kg / cm 2 .

[0038] The invention discloses an application of environmentally friendly water-based microfiber leather in daily necessities, industrial products and clothing industries.

[0039] Beneficial Effects

[0040] The present invention provides an environmentally friendly water-based microfiber leather and a preparation method and application thereof. Compared with the prior art, it has the following beneficial effects:

[0041] (1) The present invention prepares an antibacterial solution so that the amino and hydroxyl groups in its structure can interact with the microfiber staple fibers and WPU slurry by forming hydrogen bonds, etc., thereby strengthening the internal structure and improving the tensile strength of the microfiber leather. At the same time, the antibacterial solution adheres to and penetrates the fiber surface, thereby strengthening the bonding force between the fibers and improving the tear resistance. The antibacterial solution can interact with the negative charge of the microbial cell membrane, destroying the cell membrane and causing the death of the microorganisms. Its degradation products can also interfere with the metabolism of the microorganisms, slowly release the antibacterial components, and provide lasting antibacterial properties. The antibacterial agent can form tiny channels between the fibers, which is beneficial for the passage of water vapor, increases the hydrophilicity of the leather, and makes it easier for water vapor to be absorbed and transmitted. In addition, the components in the antibacterial solution can interact with the molecular chains of the WPU slurry, increasing the mobility of the molecular chain segments, making it easier for the microfiber leather to return to its original position after being folded and compressed.

[0042] (2) The present invention changes the surface properties of the fiber through the preparation of the flame retardant solution. The filling effect of the flame retardant solution strengthens the connection between the fibers and improves the tear strength. At the same time, the flame retardant solution will decompose at high temperature to produce phosphorus-containing free radicals. These free radicals can capture the highly active hydrogen free radicals and hydroxyl free radicals produced during the combustion process, thereby interrupting the chain reaction of combustion and inhibiting the spread of flames. When heated, a dense carbonized layer will be formed, covering the surface of the microfiber leather, isolating the transfer of oxygen and heat, preventing the leather from further burning, and improving the flame retardant properties of the microfiber leather.

[0043] (3) The WPU slurry prepared by the present invention can provide flexible segments, and the formed polyurethane structure has good cohesion, which gives the microfiber leather high tensile strength; the pore structure formed by the microfiber short fibers, combined with the cross-linking degree of the WPU slurry, makes the microfiber leather have certain air permeability and moisture permeability, and is comfortable to wear; and compared with some traditional leather production processes, the preparation process can reduce the use of harmful chemicals, and the water-based system of the WPU slurry is more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 The SEM images of the ultra-short fibers provided by the present invention and the ultra-short fibers immersed in an antibacterial solution are shown. DETAILED DESCRIPTION

[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Example 1

[0047] A method for preparing environmentally friendly water-based microfiber leather comprises the following preparation steps:

[0048] Step 1: Put the microfiber staple fibers into a sodium hydroxide solution for activation, and then add dilute hydrochloric acid to neutralize;

[0049] Step 2: immerse the treated microfiber staple fibers in an antibacterial solution, allow the microfiber staple fibers to fully absorb the antibacterial solution, and then squeeze out the antibacterial solution in the microfiber staple fibers;

[0050] The preparation method of the antibacterial solution is as follows: soak chitosan in a 40% sodium hydroxide solution for 20 hours and filter it; pour chloroacetic acid into 150 mL of isopropanol, stir and dissolve it to obtain a mixed solution; after it is completely dissolved, pour the product obtained by the above filtration into the mixed solution, and react it at room temperature for 24 hours; after the reaction is completed, add hydrochloric acid to adjust the pH value of the solution to 7.0, then add anhydrous ethanol to precipitate a precipitate, wash the precipitate with ionized water for 3 times, and finally place it in a drying oven at 45°C for drying; pour the dried precipitate into a sodium hydroxide solution, heat it to 50°C in a water bath, stir and react for 18 hours, and then add hydrochloric acid to neutralize it to a pH of 7.8; grind it, and then use a nano ultra-high pressure homogenizer to treat it for 20 minutes to obtain an antibacterial solution;

[0051] Step 3, immersing the ultra-short fibers in a flame retardant solution again, allowing the ultra-short fibers to fully absorb the flame retardant solution, and then squeezing out the flame retardant solution in the ultra-short fibers to obtain an ultra-short fiber composite;

[0052] The flame retardant solution was prepared by pouring 12.2 g of p-hydroxybenzaldehyde and 7.5 g of 3-aminopropanol into 125 mL of anhydrous ethanol and mixing them evenly; heating the oil bath to 50°C in an oil bath pot, stirring and reacting at a speed of 230 r / min for 1.5 hours; cooling to room temperature, filtering, washing the reaction product with deionized water for 3 times, and finally drying it in a vacuum oven at 45°C for 8 hours to obtain 4-((3-hydroxypropyl)imino)methylbenzene. Phenol; pour 9.5g of 4-((3-hydroxypropyl)imino)methylphenol and 10.5g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide into 150mL of ethanol without water, heat to 75°C, and stir at 250r / min for 4.5h; after the reaction is completed, cool to room temperature, filter, wash with anhydrous ethanol 3 times, and then dry in a vacuum oven at 55°C to constant weight to obtain a flame retardant solution;

[0053] Step 4, washing the microfiber staple fiber composite until the pH of the washing liquid is 7.5, and then drying;

[0054] Step 5, weighing, combing, mixing, laying, pre-needling, positive and negative needling are performed in sequence to form a non-woven fabric with a three-dimensional structural network;

[0055] Step 6: After the non-woven fabric is treated with plasma in a nitrogen atmosphere at a gas flow rate of 50 sccm, it is immersed in the WPU slurry for 45 minutes, and then the non-woven fabric is double-dipped and double-rolled, and the rolled base fabric is immersed in the prepared sodium sulfate solution for 3 minutes, and then infrared pre-dried, and after 10 minutes, it is transferred to a 100°C hot air oven for drying to obtain environmentally friendly water-based microfiber leather including;

[0056] The preparation method of WPU slurry is as follows: 25g of polycarbonate diol and 10g of polytetrahydrofuran are placed under vacuum dehydration at 85°C for 1.5h and then mixed; 16.55g of isophorone diisocyanate is added, and the temperature is raised to 70°C under a nitrogen atmosphere; 1.2g of dibutyltin dilaurate is added dropwise under stirring at a speed of 180r / min, and the reaction is kept warm for 3.5h; the temperature is lowered to 60°C, 12g of acetone is added, and then the mixture is stirred at 40°C for 3 hours. Add 1.5g of 2,2-dihydroxymethylpropionic acid, 0.8g of 1,4-butanediol and 1.2g of trimethylolpropane, and react for 10h respectively; cool to 35°C, add 0.85g of triethylamine, and react for 20min; add 80g of deionized water and 1g of ethylenediamine, stir and react at a speed of 1000r / min for 20min, then rotary evaporate, place in a vacuum drying oven for vacuum degassing for 45min, and obtain WPU slurry.

[0057] Example 2

[0058] A method for preparing environmentally friendly water-based microfiber leather comprises the following preparation steps:

[0059] Step 1: Put the microfiber staple fibers into a sodium hydroxide solution for activation, and then add dilute hydrochloric acid to neutralize;

[0060] Step 2: immerse the treated microfiber staple fibers in an antibacterial solution, allow the microfiber staple fibers to fully absorb the antibacterial solution, and then squeeze out the antibacterial solution in the microfiber staple fibers;

[0061] The preparation method of the antibacterial solution is as follows: soak chitosan in a 40% sodium hydroxide solution for 22 hours and filter it; pour chloroacetic acid into 160 mL of isopropanol and stir to dissolve it to obtain a mixed solution; after it is completely dissolved, pour the product obtained by the above filtration into the mixed solution and react it at room temperature for 30 hours; after the reaction is completed, add hydrochloric acid to adjust the pH value of the solution to 7.0, then add anhydrous ethanol to precipitate a precipitate, wash the precipitate with ionized water for 4 times, and finally place it in a drying oven at 50°C for drying; pour the dried precipitate into a sodium hydroxide solution, heat it to 55°C in a water bath, stir to react for 23 hours, and then add hydrochloric acid to neutralize it to a pH of 7.9; grind it, and then use a nano ultra-high pressure homogenizer to treat it for 25 minutes to obtain an antibacterial solution;

[0062] Step 3, immersing the ultra-short fibers in a flame retardant solution again, allowing the ultra-short fibers to fully absorb the flame retardant solution, and then squeezing out the flame retardant solution in the ultra-short fibers to obtain an ultra-short fiber composite;

[0063] The flame retardant solution was prepared by pouring 14 g of p-hydroxybenzaldehyde and 8.5 g of 3-aminopropanol into 140 mL of anhydrous ethanol and mixing them evenly; heating the oil bath to 60° C. in an oil bath pot, stirring and reacting at a speed of 300 r / min for 1.8 h; cooling to room temperature, filtering, washing the reaction product with deionized water for 4 times, and finally drying it in a vacuum oven at 50° C. for 10 h to obtain 4-((3-hydroxypropyl)imino)methyl Phenol; pour 10.5g of 4-((3-hydroxypropyl)imino)methylphenol and 12g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide into 180mL of ethanol without water, heat to 85°C, and stir at 300r / min for 5h; after the reaction is completed, cool to room temperature, filter, wash with anhydrous ethanol 4 times, and then dry in a vacuum oven at 60°C to constant weight to obtain a flame retardant solution;

[0064] Step 4, washing the microfiber staple fiber composite until the pH value of the washing liquid is 7.8, and then drying;

[0065] Step 5, weighing, combing, mixing, laying, pre-needling, positive and negative needling are performed in sequence to form a non-woven fabric with a three-dimensional structural network;

[0066] Step 6: After the non-woven fabric is treated with plasma in a nitrogen atmosphere at a gas flow rate of 50 sccm, it is immersed in the WPU slurry for 55 minutes, and then the non-woven fabric is double-dipped and double-rolled, and the rolled base fabric is immersed in the prepared sodium sulfate solution for 3 minutes, and then infrared pre-dried, and after 125 minutes, it is transferred to a 105°C hot air oven for drying to obtain environmentally friendly water-based microfiber leather including;

[0067] The preparation method of WPU slurry is as follows: 28g of polycarbonate diol and 14g of polytetrahydrofuran are placed under a temperature condition of 90°C for vacuum dehydration for 1.7h and then mixed; 21g of isophorone diisocyanate is added, and the temperature is raised to 75°C under a nitrogen atmosphere; 2g of dibutyltin dilaurate is added dropwise under a stirring condition of a speed of 200r / min, and the reaction is kept warm for 4h; the temperature is lowered to 63°C, 13g of acetone is added, and then 1g of 2,2-dihydroxymethylpropionic acid, 1g of 1,4-butanediol, and 2g of trimethylolpropane are added in sequence, and the reactions are respectively carried out for 12h; the temperature is lowered to 40°C, 1g of triethylamine is added, and the reaction is carried out for 305min; 95g of deionized water and 1.2g of ethylenediamine are added, and the reaction is stirred at a speed of 1100r / min for 25min, and then rotary evaporated, and placed in a vacuum drying oven for vacuum degassing for 50min to obtain WPU slurry.

[0068] Example 3

[0069] A method for preparing environmentally friendly water-based microfiber leather comprises the following preparation steps:

[0070] Step 1: Put the microfiber staple fibers into a sodium hydroxide solution for activation, and then add dilute hydrochloric acid to neutralize;

[0071] Step 2: immerse the treated microfiber staple fibers in an antibacterial solution, allow the microfiber staple fibers to fully absorb the antibacterial solution, and then squeeze out the antibacterial solution in the microfiber staple fibers;

[0072] The preparation method of the antibacterial solution is as follows: soak chitosan in a 40% sodium hydroxide solution for 24 hours and filter it; pour chloroacetic acid into 180 mL of isopropanol and stir to dissolve it to obtain a mixed solution; after it is completely dissolved, pour the product obtained by the above filtration into the mixed solution and react it at room temperature for 36 hours; after the reaction is completed, add hydrochloric acid to adjust the pH value of the solution to 7.0, then add anhydrous ethanol to precipitate a precipitate, wash the precipitate with ionized water for 5 times, and finally place it in a drying oven at 55°C for drying; pour the dried precipitate into a sodium hydroxide solution, heat it to 65°C in a water bath, stir to react for 24 hours, and then add hydrochloric acid to neutralize it to a pH of 8; grind it, and then use a nano ultra-high pressure homogenizer to treat it for 30 minutes to obtain an antibacterial solution;

[0073] Step 3, immersing the ultra-short fibers in a flame retardant solution again, allowing the ultra-short fibers to fully absorb the flame retardant solution, and then squeezing out the flame retardant solution in the ultra-short fibers to obtain an ultra-short fiber composite;

[0074] The flame retardant solution was prepared by pouring 16 g of p-hydroxybenzaldehyde and 9.5 g of 3-aminopropanol into 160 mL of anhydrous ethanol and mixing them evenly; heating the oil bath to 70 ° C in an oil bath pot, stirring at a speed of 350 r / min for 2 hours; cooling to room temperature, filtering, washing the reaction product with deionized water for 5 times, and finally drying it in a vacuum oven at 60 ° C for 12 hours to obtain 4-((3-hydroxypropyl)imino)methylbenzene. Phenol; pour 12.5g of 4-((3-hydroxypropyl)imino)methylphenol and 14g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide into 200mL of ethanol without water, heat to 95°C, and stir at 400r / min for 6h; after the reaction is completed, cool to room temperature, filter, wash with anhydrous ethanol 4 times, and then dry in a vacuum oven at 65°C to constant weight to obtain a flame retardant solution;

[0075] Step 4, washing the microfiber staple fiber composite until the pH value of the washing liquid is 8, and then drying;

[0076] Step 5, weighing, combing, mixing, laying, pre-needling, positive and negative needling are performed in sequence to form a non-woven fabric with a three-dimensional structural network;

[0077] Step 6: After the non-woven fabric is treated with plasma in a nitrogen atmosphere at a gas flow rate of 50 sccm, it is immersed in the WPU slurry for 65 minutes, and then the non-woven fabric is double-dipped and double-rolled, and the rolled base fabric is immersed in the prepared sodium sulfate solution for 3 minutes, and then infrared pre-dried, and after 15 minutes, it is transferred to a 110°C hot air oven for drying to obtain environmentally friendly water-based microfiber leather including;

[0078] The preparation method of WPU slurry is as follows: 30g of polycarbonate diol and 18g of polytetrahydrofuran are placed under vacuum dehydration at 95°C for 2h and then mixed; 25g of isophorone diisocyanate is added, and the temperature is raised to 80°C under a nitrogen atmosphere; 2.5g of dibutyltin dilaurate is added dropwise under stirring at a speed of 220r / min, and the reaction is kept warm for 4.5h; the temperature is lowered to 65°C, 15g of acetone is added, and 2 .5g of 2,2-dihydroxymethylpropionic acid, 1.25g of 1,4-butanediol, and 2.8g of trimethylolpropane were reacted for 15h respectively; the temperature was lowered to 45°C, 1.3g of triethylamine was added, and the reaction was carried out for 35min; 110g of deionized water and 1.5g of ethylenediamine were added, and the reaction was stirred at a speed of 1200r / min for 30min, and then rotary evaporated, and placed in a vacuum drying oven for vacuum degassing for 60min to obtain WPU slurry.

[0079] Comparative Example 1

[0080] Compared with Example 1, the difference is that no flame retardant solution is added; the rest remains unchanged.

[0081] Comparative Example 2

[0082] Compared with Example 1, the difference is that no antibacterial solution is added; the rest remains unchanged.

[0083] Comparative Example 3

[0084] Compared with Example 1, the difference is that the WPU slurry is replaced by PU resin; the rest remains unchanged.

[0085] Mechanical properties test: The test was carried out in accordance with QB / T 4909-2016; the results are shown in Table 1.

[0086] Moisture permeability test: Tested in accordance with GB / T 12704.2-2009; the results are shown in Table 1; the moisture permeability calculation formula is:

[0087]

[0088] Where WVT is the water vapor transmission rate, mg / cm 2 h; m0 is the initial mass of the sample, mg; m1 is the mass of the sample after moisture permeation, mg; S is the area of ​​the sample, cm 2; t is the moisture permeation time of the sample, h.

[0089] Crease recovery performance test: Referring to GB / T3819, the NF8541 fully automatic fabric wrinkle elasticity tester was used for testing; the results are shown in Table 1.

[0090] Table 1

[0091] Breaking strength / MPa Slow rebound angle / ° Specific compression rebound rate / % Example 1 31.28 130.96 4.99 Example 2 31.09 128.73 4.56 Example 3 28.75 127.06 4.27 Comparative Example 1 21.35 115.68 3.21 Comparative Example 2 23.07 93.18 2.19 Comparative Example 3 20.54 98.35 2.34

[0092] Limiting oxygen index (LOI) test: Test in accordance with GB / T 5454-1997.

[0093] Vertical burning (UL-94) performance test: Tested in accordance with GB / T 5455-2014.

[0094] Antibacterial performance test: Tested in accordance with GB / T 43823-2024.

[0095]

[0096] like Figure 1 As shown, the microfibers soaked in the antibacterial solution have fewer regenerated membranes, smaller pore sizes, and a very smooth surface compared to the microfibers not soaked in the antibacterial solution.

[0097] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.

[0098] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0099] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An environmentally friendly water-based microfiber leather, characterized in that: The environmentally friendly water-based microfiber leather comprises the following components: microfiber staple fibers, flame retardant solution, antibacterial solution, and WPU slurry; Wherein, the preparation method of WPU slurry is: Ⅰ. Mix 25-30g of polycarbonate diol and 10-18g of polytetrahydrofuran under vacuum dehydration at 85-95°C for 1.5-2h; Ⅱ. Add 16.5-25g of isophorone diisocyanate and raise the temperature to 70-80°C under nitrogen atmosphere; III. Under stirring conditions, add 1.2-2.5 g of dibutyltin dilaurate dropwise and keep the reaction warm for 3.5-4.5 hours; IV. Cool down to 60-65°C, add 12-15g of acetone, then add 1.5-2.5g of 2,2-dihydroxymethylpropionic acid, 0.8-1.25g of 1,4-butanediol, and 1.2-2.8g of trimethylolpropane, and react for 10-15h respectively; Ⅴ. Cool down to 35-45°C, add 0.85-1.3 g of triethylamine, and react for 20-35 min; VI. Add 80-110 g of deionized water and 1-1.5 g of ethylenediamine, stir and react for 20-30 min, then rotary evaporate, place in a vacuum drying oven for vacuum degassing for 45-60 min, and obtain WPU slurry; Among them, in the III, the stirring speed is 180-220r / min; in the VI, the stirring speed is 1000-1200r / min.

2. The environmentally friendly water-based microfiber leather according to claim 1, characterized in that: The preparation method of the flame retardant solution is: S1. Pour 4-((3-hydroxypropyl)imino)methylphenol and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide into anhydrous ethanol, raise the temperature to 75-95° C., and stir at a speed of 250-400 r / min to react for 4.5-6 h; S2. After the reaction is completed, cool to room temperature, filter, wash with anhydrous ethanol 3-4 times, and then dry in a vacuum oven at 55-65°C to constant weight to obtain a flame retardant solution.

3. The environmentally friendly water-based microfiber leather according to claim 2, characterized in that: During the preparation of the flame retardant solution, the added amounts of the components are: 9.5-12.5 g of 4-((3-hydroxypropyl)imino)methylphenol, 10.5-14 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 150-200 mL of anhydrous ethanol.

4. The environmentally friendly water-based microfiber leather according to claim 3, characterized in that: In S1, the preparation process of 4-((3-hydroxypropyl)imino)methylphenol is: S11, pouring p-hydroxybenzaldehyde and 3-aminopropanol into anhydrous ethanol and mixing evenly; S12, heat the oil bath to 50-70°C, stir and react at a speed of 230-350 r / min for 1.5-2 h; S13, cooling to room temperature, filtering, washing the reaction product with deionized water for 3-5 times, and finally drying it in a vacuum oven at 45-60° C. for 8-12 hours to obtain 4-((3-hydroxypropyl)imino)methylphenol.

5. The environmentally friendly water-based microfiber leather according to claim 4, characterized in that: During the preparation of the 4-((3-hydroxypropyl)imino)methylphenol, the added amounts of the components are: 12.2-16 g of p-hydroxybenzaldehyde, 7.5-9.5 g of 3-aminopropanol, and 125-160 mL of anhydrous ethanol.

6. The environmentally friendly water-based microfiber leather according to claim 1, characterized in that: The preparation method of the antibacterial solution is: (1) Soak chitosan in 40% sodium hydroxide solution for 20-24 hours and filter; (2) Pour chloroacetic acid into 150-180 mL of isopropanol and stir to dissolve to obtain a mixed solution; (3) After complete dissolution, the product filtered in (1) is poured into the mixed solution in (2) and reacted at room temperature for 24-36 hours; (4) After the reaction is completed, hydrochloric acid is added dropwise to adjust the pH value of the solution to 7.0, and then anhydrous ethanol is added to precipitate a precipitate, and then the precipitate is washed with deionized water for 3-5 times, and finally placed in a drying oven at 45-55°C for drying; (5) Pour the dried precipitate into a sodium hydroxide solution, heat it to 50-65°C in a water bath, stir and react for 18-24 hours, then add hydrochloric acid dropwise to neutralize to a pH of 7.8-8; (6) Grinding, and then treating with a nano ultra-high pressure homogenizer for 20-30 minutes to obtain an antibacterial solution.

7. A method for preparing the environmentally friendly water-based microfiber leather according to claim 1, characterized in that: The method comprises the following preparation steps: Step 1: Put the microfiber staple fibers into a sodium hydroxide solution for activation, and then add dilute hydrochloric acid to neutralize; Step 2: immerse the treated microfiber staple fibers in an antibacterial solution, allow the microfiber staple fibers to fully absorb the antibacterial solution, and then squeeze out the antibacterial solution in the microfiber staple fibers; Step 3, immersing the ultra-short fibers in a flame retardant solution again, allowing the ultra-short fibers to fully absorb the flame retardant solution, and then squeezing out the flame retardant solution in the ultra-short fibers to obtain an ultra-short fiber composite; Step 4, washing the microfiber staple fiber composite until the pH value of the washing liquid is no more than 8, and then drying; Step 5, weighing, combing, mixing, laying, pre-needling, positive and negative needling are performed in sequence to form a non-woven fabric with a three-dimensional structural network; Step six: treat the non-woven fabric with plasma in a nitrogen atmosphere at a gas flow rate of 50 sccm, immerse it in the WPU slurry for 45-65 minutes, and then perform double dipping and double rolling on the non-woven fabric. Immerse the rolled base fabric in the prepared sodium sulfate solution for 3 minutes, and then pre-dry it with infrared. After 10-15 minutes, transfer it to a 100-110°C hot air oven for drying to obtain environmentally friendly water-based microfiber leather.

8. The method for preparing an environmentally friendly water-based microfiber leather according to claim 7, characterized in that: In step 6, the first pressure is 30kg / cm 2 , the second pressure is 10kg / cm 2 .

9. Application of environmentally friendly water-based microfiber leather in daily necessities, industrial products and clothing industries.